PENGEMBANGAN KOMPETENSI SDM DI ERA TRANSFORMASI DIGITAL: STRATEGI UPSKILLING DAN RESKILLING UNTUK MENINGKATKAN PRODUKTIVITAS DAN DAYA SAING KERJA - Jackson Yumame; Ramdan Yusuf; Edy Sijaya (CV. Lafadz Jaya, 2026)
Rapid advances in digital technology have transformed the world of work and necessitate the development of human resource competencies that are adaptable to digital transformation. This article aims to analyse the concept and urgency of human resource competency development in the era of digital transformation, as well as to identify effective upskilling and reskilling strategies to enhance productivity and workplace competitiveness. The method used is a literature review with a qualitative approach. The research findings indicate that the development of HR competencies is both an urgent necessity and a strategic investment for organisational sustainability. The widening skills gap is a major challenge that must be addressed through systematic upskilling and reskilling strategies. Effective strategies include identifying competency needs, designing relevant curricula, utilising learning technologies such as Learning Management Systems and digital learning, and fostering a culture of continuous learning. The research indicates that employees who participate in upskilling and reskilling programmes experience a productivity increase of up to 30%, higher engagement, and improved staff retention. Integrating talent development strategies with organisational needs can strengthen a company’s competitiveness in the global market and ensure that technology investments deliver optimal results. Support from transformational leadership and synergy between organisations and the government are key factors in the success of competency development programmes in the digital age.